Li3V2(PO4)3 sintering atmosphere optimisation for its integration in all-solid-state batteries - Fabre, Timothée; Lachal, Marie; Raj, Hari; Pralong, Valérie; Bouchet, Renaud; Steil, Marlu César (Journal of the European Ceramic Society, 2025)
Integration of active materials into the architecture of all-solid-state batteries represents a significant scientific inquiry. Li3V2(PO4)3 (LVP), a positive and negative electrode active material for Li-ion batteries, has been subject to extensive research to elucidate its electrochemical behaviour during cycling processes. However, the comprehensive analysis of its thermal behaviour under different sintering atmosphere conditions has remained underexplored, particularly in the context of its compatibility with solid electrolytes. This study presents a meticulous study of sintering process under different atmospheres with precise control over oxygen partial pressure. Interestingly, we were able to sinter LVP and obtain dense, pure ceramic phase under slightly oxidising atmosphere, characterized by conductivity properties analogous to those observed in samples sintered under Ar/H2 conditions. The findings of this investigation contribute to the understanding of the optimal conditions required for the sintering of LVP, paving the way for the co-sintering of this material with inorganic solid electrolyte unstable under reducing atmosphere, such as LATP.